An Axiomatic Approach to Measurable Utility - Herstein, I. N.; Milnor, John (Econometrica, 1953)
Previous treatments of this approach brought topological considerations of the prospects space into the axioms. In this paper considerations of the topology of the prospect space itself are removed, the previous axioms are weakened an infinite number of sure prospects are allowed. On the basis of these axioms the existence of a measurable utility is established.